2005
DOI: 10.1110/ps.051431605
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous optimization of enzyme activity and quaternary structure by directed evolution

Abstract: Natural evolution has produced efficient enzymes of enormous structural diversity. We imitated this natural process in the laboratory to augment the efficiency of an engineered chorismate mutase with low activity and an unusual hexameric topology. By applying two rounds of DNA shuffling and genetic selection, we obtained a 400-fold more efficient enzyme, containing three non-active-site mutations. Detailed biophysical characterization of the evolved variant suggests that it exists predominantly as a trimer in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Although the preferences observed at positions 30, 40, and 42 are modest and not readily rationalized, the strong selection for aspartate at positions 15 and 18 in both libraries, and the absolute requirement for lysine at position 29 in the EcCM library, can be explained in structural terms. For example, the aspartates at positions 15 and 18 are second shell residues that can form salt bridges with the essential active site residues Arg51 and Arg28, and thereby help preorganize the binding pocket for catalysis 25, 29, 34. Such interactions are evidently much more important for the less stable protein, since 100% of active EcCM variants have an aspartate at position 18, and 81% have this residue at position 15, compared to only 85% and 75% aspartate at the respective positions in active MjCM mutants.…”
Section: Resultsmentioning
confidence: 99%
“…Although the preferences observed at positions 30, 40, and 42 are modest and not readily rationalized, the strong selection for aspartate at positions 15 and 18 in both libraries, and the absolute requirement for lysine at position 29 in the EcCM library, can be explained in structural terms. For example, the aspartates at positions 15 and 18 are second shell residues that can form salt bridges with the essential active site residues Arg51 and Arg28, and thereby help preorganize the binding pocket for catalysis 25, 29, 34. Such interactions are evidently much more important for the less stable protein, since 100% of active EcCM variants have an aspartate at position 18, and 81% have this residue at position 15, compared to only 85% and 75% aspartate at the respective positions in active MjCM mutants.…”
Section: Resultsmentioning
confidence: 99%
“…18,[22][23][24][36][37][38] Here we show for the first time the construction of a functional heterodimeric CM. Simply cleaving the dimer-spanning N-terminal helix of MjCM to yield a one-helix and a three-helix fragment abolishes enzyme function in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 75%
“…18,[21][22][23][24] Insertion of short peptide sequences into the middle of the dimer-spanning N-terminal helix converts the natural homodimer into monomers (mMjCM), 18 trimers, 22 and hexamers. 22 The tolerance of the N-terminal helix to disruption between residues 21 and 22 also makes this an attractive cleavage site for the generation of a heterodimeric mutase [ Fig. 1(A)].…”
Section: Design Of a Heterodimeric Chorismate Mutasementioning
confidence: 99%
“…In fact, natural enzymes that are chemically modified, can catalyze the same biochemical reactions much faster. 7 Recently, Reuveni et al 8,9 proposed a new way of optimizing the rates of enzymatic reactions. They showed that these reactions can be accelerated by increasing the rate of substrate unbinding from the enzyme–substrate complex when 8 “(i) substrate concentrations are high; (ii) the unbinding rate is low; and (iii) the coefficient of variation associated with the distribution of catalytic times is larger than unity.”…”
Section: Introductionmentioning
confidence: 99%